A workshop aimed at empowering general practitioners with the latest hypertension management guideline - Ismail, Ilham Ameera; Kamaruddin, Khairatul Nainey (Faculty of Medicine, 2025)
On 2–3 August 2025, a two-day seminar & Workshop on the management of hypertension was held at the Royale Chulan Damansara Hotel with the theme of “upskilling practices, updating knowledge”. It was organised by the Persatuan Doktor-Doktor Islam Malaysia (PERDIM), in collaboration with the Academy of Family Physicians of Malaysia (AFPM) and the Faculty of Medicine, Universiti Teknologi MARA (UiTM). The event brought together over 100 general practitioners (GPs) from across the country with a shared goal, to strengthen clinical competence in the diagnosis, risk stratification, and management of hypertension according to the Malaysian Clinical Practice Guidelines (CPG) on Hypertension.